A Comparison of Tertiary Drug Resources' Consistency Regarding Drug-Drug Interactions of Adjunctive Analgesics. (February 2021) - Lang, Andrew; Veronin, Michael A.; Reinert, Justin P.
Background: Health care providers routinely rely on tertiary drug information resources to affirm knowledge or proactively verify the safety and efficacy of medications. Though all patient care areas are affected, the reliability of these resources is perhaps nowhere as poignant as it is in high-acuity settings, including the emergency department and the intensive care unit. As providers seek to identify adjunctive analgesics for acute pain in these areas, they must be able to rely on the integrity to whichever resource their institution has granted access.Objective: To determine the congruency of drug-drug interaction information found on 3 tertiary drug resources.Methods: A drug-drug interaction analysis was conducted on Micromedex, Lexicomp, and Medscape. Adjunctive analgesics included dexmedetomidine and ketamine, which were compared with the intravenous opioid products morphine, fentanyl, and hydromorphone.Results: Significant discrepancies were appreciated with regard to the severity of drug-drug interactions. In addition, the heterogeneity in which reaction severity and likelihood are described by each respective resource makes direct comparisons difficult. Interaction warnings for dexmedetomidine and fentanyl included a "major interaction" from Micromedex, whereas Lexicomp did not identify a risk and Medscape only recommended increased monitoring on the grounds of respiratory and central nervous system depression.Conclusions: Health care providers must remain vigilant when reviewing tertiary drug information resources. Pharmacists possess the training and skills necessary to assist interdisciplinary medical teams in providing optimal patient care through evaluating and applying the information gleaned from these resources.